Identification and genomic analyses of a novel endophytic actinobacterium Streptomyces endophytica sp. nov. with potential for biocontrol of yam anthracnose - Zhou, Shuangqing; Zhou, Yifan; Li, Chengui; Wu, Wenqiang; Xu, Yun; Xia, Wei; Huang, Dongyi; Huang, Xiaolong (Frontiers in Microbiology, 2023)
Anthracnose disease caused by Colletotrichum gloeosporioides is one of the devastating diseases of yams (Dioscorea sp.) worldwide. In this study, we aimed to isolate endophytic actinobacteria from yam plants and to evaluate their potential for the control of yam anthracnose based on bioassays and genomic analyses. A total of 116 endophytic actinomycete strains were isolated from the surface-sterilized yam tissues from a yam orchard in Hainan Province, China. In total, 23 isolates showed antagonistic activity against C. gloeosporioides. An endophytic actinomycete, designated HNM0140T, which exhibited strong antifungal activities, multiple biocontrol, and plant growth-promoting (PGP) traits was subsequently selected to colonize in the tissue-cultured seedlings of yam and was tested for its in vivo biocontrol potential on yam anthracnose. The results showed that treatment with strain HNM0140T markedly reduced the severity and incidence of yam anthracnose under greenhouse conditions. Morphological and chemotaxonomic analyses showed that strain HNM0140T was assigned to the genus Streptomyces. Phylogenetic analysis based on the 16S rRNA gene sequences indicated that strain HNM0140T formed a separate cluster together with Streptomyces lydicus ATCC 25470T (99.45%), Streptomyces chattanoogensis NRRL ISP-5002T (99.45%), and Streptomyces kronopolitis NEAU-ML8T (98.97%). The phylogenomic tree also showed that strain HNM0140T stably clustered with Streptomyces lydicus ATCC 25470T. The ANI and dDDH between strain HNM0140T and its closest related-type species were well below the recommended thresholds for species demarcation. Hence, based on the phylogenetic, genomic, and phenotypic analyses, strain HNM0140T should represent a new streptomycete species named Streptomyces endophytica sp. nov. Genomic analysis revealed that strain HNM0140T harbored 18 putative BGCs for secondary metabolites, some PGP-related genes, and several genes coding for antifungal enzymes. The presented results indicated that strain HNM0140T was a promising biocontrol agent for yam anthracnose.